ضمانات إدارة قاضي التحقيق في المملكة العربية السعودية وأثرها على استقلاليَّته في ضوء الشريعة الإسلامية والمواثيق الدولية = Guarantees of management of the investigating judge in the Kingdom of Saudi Arabia and their impact on his independence in the light of Islamic law and international treaties - Salim, Yaser; Negasi, Mohamed Ibrahim; Laeba, Muhammad (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
يعدُّ القضاء الضامن الأساس لحقوق الأفراد وحرياتهم من أ ي تعسُّف أو استبداد؛ وأن استقلالية القضاء تضمن له من أي تدخل أو تأثير، كما أنها تحتاج لعدد من الضمانات لتقوم بحماية القضاء، والتي منها ضمانات إدارة قاضي التحقيق. لذا تهدف هذه الورقة لكشف العلاقة بين إدارة قاضي التحقيق في القانون السعودي واستقلاليته، وما تشترطه استقلاليته من ضمانات في إدارته. حيث تتمثل إشكالية البحث في مدى كفالة القانون السعودي للضمانات المشترطة لاستقلالية قاضي التحقيق في كيفيَّة إدارته. وتكمن أهمية البحث في تقييم هذه الضمانات، ومدى اتفاقها مع الش ريعة الإسلامية والمواثيق الدولية، وس د ما وُجِّدَ بها من ثغرات. وقد استخدم الباحث المنهج الوصفي والتحليلي والمقارن مراعاة لطبيعة الدراسة. وأظهرت نتائج الدراسة وجود بعض الإشكالات والثغرات في ضمانات استقلال قاضي التحقيق في القانون السعودي المتعلق بإدارته، وأوصى الباحث ببعض التعديلات في هذا القانون ليتحقق ضمان استقلاله، والتي تم اقتراحها في خاتمة النتائج. ********************************************** The judiciary is regarded as the primary protector of the rights and freedoms of individuals from any abuse or tyranny; and its independence protects it form any intervention and influence. Likewise, a number of guarantees are needed to ensure the protection of judiciary among which are guarantees for the management of investigating judge. Therefore, this research aims at revealing the relationship between the management of the investigating judge in the Saudi law, his independence and the security that the independence of his management requires. The problem statement of this research is reflected in the extent to which Saudi law ensures the guarantees that are required for independence of the investigating judge in his way of administration. The importance of the paper lies in the assessment of these guarantees, the extent of their agreement with Islamic law and international treaties, and bridging gaps between them. Considering the nature of the study, the researcher adopts the descriptive, analytical and comparative approaches. The results of the study show the existence of some problems and gaps in the guarantees for independence of the investigating judge related to his management. The researcher recommends some amendments to this law to ensure the guarantee for his independence, which have been proposed in the end of the findings.